Prognosis of asymptomatic endolymphatic hydrops in healthy volunteers: A five‐year cohort study - Takahiro Kimura; Tadashi Kitahara; Tadao Okayasu; Masaharu Sakagami; Tomoyuki Shiozaki; Hiroshi Inui; Toshizo Koizumi; Mariko Kakudo (Laryngoscope Investigative Otolaryngology)
Abstract Background This study aimed to clarify the prognosis of asymptomatic endolymphatic hydrops (EH) in healthy volunteers via five‐year follow‐ups with inner ear magnetic resonance imaging (MRI). Methods Inner ear MRI was performed on 115 participants recruited as controls in a previous study on Meniere's disease. The endolymphatic space was visualized using Naganawa's method of contrast‐enhanced MRI with intravenous gadolinium injection and evaluated using Nakashima's method of 2D imaging analysis. Results Cochlear or vestibular EH was present in 7.0% of participants (n = 8), with all cases being unilateral (laterality), moderate (severity), and asymptomatic (onset). Only cochlear‐localized EH, only vestibular‐localized EH, and both EH were present in 1.7% (n = 2) (C group), 4.3% (n = 5) (V group), and 0.9% (n = 1) (CV group) of participants, respectively. Conducting inner ear MRI after 5 years showed that EH had almost disappeared in two participants in the C and V groups (4/8, 50.0%). EH was still present in three participants in the V group and one in the CV group (4/8, 50.0%). One participant in the V group and another in the CV group presented with residual inner ear EH and developed typical symptomatic Meniere's disease (2/8, 25.0%). Conclusions Approximately 7% of healthy participants showed asymptomatic EH. Therefore, EH is not the definitive marker for making a diagnosis of Meniere's disease or the suitable predictor for the development of Meniere's disease. Among these participants, 25% maintained EH and subsequently developed typical Meniere's disease within the next 5 years. Schellong‐positive participants maintained persistent EH in the inner ear, and participants with higher scores on the self‐rating depression scale developed Meniere's symptoms after 5 years. Level of evidence 2a